Respuesta :

Answer: Below

Step-by-step explanation:

Using the information, we can see that they all refer to Elena as a marker for how much they walked, directly or indirectly.

Let's use E for Elena, J for Jada, and L for Lin.

E + 4 = J

E + 6 = L

E = E

We know they all walked a total of 37 miles.

J + L + E = 37

(E + 4) + (E + 6) + E = 37

Simplify.

3E + 10 = 37

3E = 27

E = 9

Using E is 9, we find that:

Elena walked 9 miles

Lin walked 15 miles

Jana walked 13 miles

13 + 15 + 9 = 37, so our answer checks out.

Solution:

We know that:

  • [tex]Jada + Elena + Lin = 37 \space\ miles[/tex]
  • [tex]Jada = 4 + Elena[/tex]
  • [tex]Lin = 2 + Jada[/tex]

Finding the distance each walked:

  • [tex]Jada + Elena + Lin = 37 \space\ miles[/tex]

Add 4 both sides

  • => [tex]Jada + Elena + 4 + Lin = 37 + 4[/tex]
  • => [tex]Jada + Jada + Lin = 41 \space\ miles[/tex]                                [tex][Jada = 4 + Elena][/tex]
  • => [tex]Jada + Jada + Jada + 2 = 41 \space\ miles[/tex]                          [tex][Lin = Jada + 2][/tex]

Changing "Jada + Jada + Jada" to "3(Jada)"

  • => [tex]3(Jada) + 2 = 41 \space\ miles[/tex]

Subtracting 2 both sides:

  • => [tex]3(Jada) = 41 - 2[/tex]
  • => [tex]3(Jada) = 39 \space\ miles[/tex]

Divide 3 both sides:

  • => [tex]3(Jada) = 39 \space\ miles[/tex]
  • => [tex]\frac{3(Jada)}{3} = \frac{39 \space\ miles}{3}[/tex]
  • => [tex]\bold{Jada} = \bold{13 \space\ miles}[/tex]

Substituting the miles Jada walked into the equation "Jada = 4 + Elena"

  • [tex]Jada = 4 + Elena[/tex]
  • => [tex]13 = 4 + Elena[/tex]

Subtract 4 both sides:

  • => [tex]13 - 4 = 4 - 4 + Elena[/tex]
  • => [tex]\bold{Elena} = \bold{9 \space\ miles}[/tex]

Substituting the miles Jada walked into the equation "Lin = 2 + Jada"

  • => [tex]Lin = 2 + 13[/tex]
  • => [tex]\bold{Lin} = \bold{15 \space\ miles}[/tex]